Karakteristik Arsitektur Rumah Adat Bugis: Studi Komparasi Rumah Adat Lapinceng Barru dan Sao Mario Soppeng - Akmal Baharuddin; Bakhrani A. Rauf; Rahmat Rizal (Universitas Negeri Makassar, 2026)
Abstract. Traditional architecture refers to buildings whose form, variety, and construction methods are inherited from generation to generation. This study aims to identify the architectural characteristics and to describe the similarities and differences between the traditional house of Lapinceng in Barru Regency and the Bugis traditional house of Sao Mario in Batu-Batu, Soppeng Regency, in terms of spatial orientation, floor plan and form, materials, structure and construction, and ornamental aspects. A qualitative approach with a descriptive method was applied through four stages: data selection, data presentation, analysis, and conclusion drawing. The findings reveal significant differences between the two traditional houses in terms of floor plan, facade, materials used, structural system, construction method, and ornamentation. Both houses share the saoraja classification, knock-down construction system, and the use of alliri as the primary structural element. The influence of science, technology, and cultural interaction since the colonial period has shaped the current form of Buginese noble houses. Periodic preservation efforts by both owners and the government are essential to sustain this traditional Bugis architectural heritage as a national cultural asset.Keywords: Traditional house, architectural characteristics, Lapinceng, Sao Mario, Bugis